Supplementation of heat‐inactivated Bacillus clausii DE5 in diets for grouper, Epinephelus coioides, improves feed utilization, intestinal and systemic immune responses and not growth performance. (4th September 2017) - Wang, J.; Yang, H.‐L.; Xia, H.‐Q.; Ye, J.‐d.; Lu, K.‐L.; Hu, X.; Feng, Y.; Ruan, L.; Sun, Y.‐Z.
Abstract: In recent years, more and more attentions have been paid to the development and application of probiotics in aquaculture, and viable probiotics have been extensively studied, while rare information was available about inactivated probiotics in aquaculture. Therefore, in this study, a feeding trial was designed to investigate the effect of dietary supplementation of heat‐inactivated probiotic Bacillus clausii DE5 on growth performance, immune response and key immune genes expression in head kidney and intestine in grouper Epinephelus coioides . Fish were fed for 60 days with control diet (C) and two experimental diets containing 1.0 × 10 8 CFU/g live (T1) and heat‐inactivated (T2) B. clausii DE5, respectively. The probiotic treatments did not affect the final weight, weight gain (WG) and specific growth rate (SGR) of E. coioides at days 30 and 60 ( p > .05), while both heat‐inactivated and live B. clausii DE5 significantly decreased the feed intake and feed conversion ratio (FCR) at day 60 ( p < .05). Serum lysozyme activity and complement C3 level in the two probiotic treatments were significantly higher than those in the control ( p < .05). The lysozyme activity and complement C3 level at day 60 were significantly higher than those at day 30 ( p < .05), while no significant interaction effect between diet and administration date was observed. Moreover, the heat‐inactivated B. clausii DE5 significantly improved the expression of TLR5, pro‐inflammatory cytokines (IL‐8 and IL‐1β) and TGF‐β1 in head kidney and intestine ( p < .05), while the live probiotic did not show any significant effect on the expression of these key immune‐related genes in head kidney and intestine. These results indicate that dietary supplementation of heat‐inactivated B. clausii DE5 effectively improved feed utilization and both the local and systemic immune responses of E. coioides .